Efect of crosslinking concentration on properties of 3-(trimethoxysilyl) propyl methacrylate/N-vinyl pyrrolidone gels - Mohammed, Ameen Hadi; Ahmad, Mansor; Ibrahim, Nor Azowa; Zainuddin, Norhazlin (SpringerOpen, 2018)
Background: The incorporation of two different monomers, having different properties, in the same polymer molecule leads to the formation of new materials with great scientific and commercial importance. The basic requirements for polymeric materials in some areas of biomedical applications are that they are hydrophilic, having good mechanical and thermal properties, soft, and oxygen-permeable. Results: A series of 3-(trimethoxysilyl) propyl methacrylate/N-vinyl pyrrolidone (TMSPM/NVP) xerogels containing different concentration of ethylene glycol dimethacrylate (EGDMA) as crosslinking agent were prepared by bulk polymerization to high conversion using BPO as initiator. The copolymers were characterized by FTIR. The corresponding hydrogels were obtained by swelling the xerogels in deionized water to equilibrium. Addition of EGDMA increases the transparency of xerogels and hydrogels. The minimum amount of EGDMA required to produce a transparent xerogel is 1%. All the Swelling parameters, including water content (EWC), volume fraction of polymer (ϕ2) and weight loss during swelling decrease with increasing EGDMA. Young's and shear modulus (E and G) increase as EGDMA increases. The hydrogels were characterized in terms of modulus cross-linking density (v e and v t ) and polymer-solvent interaction parameters (χ). Thermal properties include TGA and glass transition temperature (Tg) enhance by adding EGDMA whereas the oxygen permeability (P) of hydrogels decreases as water content decrease. Conclusions: This study prepared and studied the properties for new copolymer (TMSPM-co-NVP) contains different amounts of (EGDMA). These copolymers possess new properties with potential use in different biomedical applications. The properties of the prepared hydrogels are fit with the standard properties of materials which should be used for contact lenses.